Chromosomal Evolution and Apomixis in the Cruciferous Tribe Boechereae - Mandáková, Terezie; Hloušková, Petra; Windham, Michael D.; Mitchell-Olds, Thomas; Ashby, Kaylynn; Price, Bo; Carman, John; Lysak, Martin A. (Frontiers in Plant Science, 2020)
The mustard family (Brassicaceae) comprises several dozen monophyletic clades usually ranked as tribes. The tribe Boechereae plays a prominent role in plant research due to the incidence of apomixis and its close relationship to Arabidopsis. This tribe, largely confined to western North America, harbors nine genera and c. 130 species, with >90% of species belonging to the genus Boechera. Hundreds of apomictic diploid and triploid Boechera hybrids have spurred interest in this genus, but the remaining Boechereae genomes remain virtually unstudied. Here we report on comparative genome structure of six genera (Borodinia, Cusickiella, Phoenicaulis, Polyctenium, Nevada, and Sandbergia) and three Boechera species as revealed by comparative chromosome painting (CCP). All analyzed taxa shared the same seven-chromosome genome structure. Comparisons with the sister Halimolobeae tribe (n = 8) showed that the ancestral Boechereae genome (n = 7) was derived from an older n = 8 genome by descending dysploidy followed by the divergence of extant Boechereae taxa. As tribal divergence post-dated the origin of four tribe-specific chromosomes, it is proposed that these chromosomal rearrangements were a key evolutionary innovation underlaying the origin and diversification of the Boechereae in North America. Although most Boechereae genera exhibit genomic conservatism, intra-tribal cladogenesis has occasionally been accompanied by chromosomal rearrangements (particularly inversions). Recently, apomixis was reported in the Boechereae genera Borodinia and Phoenicaulis. Here, we report sexual reproduction in diploid Nevada, diploid Sandbergia, and tetraploid Cusickiella and aposporous apomixis in tetraploids of Polyctenium and Sandbergia. In sum, apomixis is now known to occur in five of the nine Boechereae genera.